Penelitian E-Government di Propinsi Jawa Barat: Kajian Pustaka Sistematis - Hediyanto, Umar Yunan Kurnia Septo (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2018)
Assessment of the implementation e-government in West Java Province has decreased, despite not having an impact on increasing the development of egovernment in Indonesia compared with other countries in the world that experienced a rating increase to 107th position in 2018. Seeing the development of e-government in West Java Province makes a necessity to improve its quality so that it can have an impact on increasing Indonesia's ranking in the top position in the future. For this reason, a state of the art mapping of e-government research is needed in West Java Province based on the results of a systematic literature review. By focusing on five main steps, namely identification of research, selection of primary studies, assessment of study quality, data extraction and monitoring, and data synthesis. In addition to the five main steps, this research will look at three aspects in the design of e-government, namely aspects of technology, people and processes. The sources used in this study are journals and proceedings of seminars taken from the Google Scholar database for five years from 2014 to 2018. The key words used in searching the Google Scholar database are